Self-persuasion: Evidence from field experiments at international debating competitions - Peter Schwardmann; Egon Tripodi; Joël J. van der Weele (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
Laboratory evidence shows that when people have to argue for a given position, they persuade themselves about the position's factual and moral superiority. Such self-persuasion limits the potential of communication to resolve conflict and reduce polarization. We test for this phenomenon in a field setting, at international debating competitions that randomly assign experienced and motivated debaters to argue one side of a topical motion. We find self-persuasion in factual beliefs and confidence in one's position. Effect sizes are smaller than in the laboratory, but robust to a one-hour exchange of arguments and a ten-fold increase in incentives for accuracy.
Keywords: C93; D72; D83; D91; 330